Effects of static and dynamic stretching on force sense, dynamic flexibility and reaction time of children - Chatzopoulos, D.; Doganis, G.; Lykesas, G.; Koutlianos, N.; Galazoulas, C.; Bassa, E. (The Open Sports Sciences Journal, 2019)
Background: Traditionally, stretching protocols are basic components of warm-up aiming to improve performance and reduce injuries. However, the literature suggests that different stretching protocols during warm-up may have diverse effects on performance. Objective: The purpose of this study was to compare the acute effects of three different stretching protocols on force sense, dynamic flexibility, reaction time and movement time. Methods: The study included twenty-five participants who were TaeKwonDo young male players (age = 11.78 ± 1.66 years.). All the participants performed one of the following protocols on different days: (a) 5 min jogging followed by 3 min Static Stretching (SS), (b) 5 min jogging followed by 3 min Dynamic Stretching (DS), and (c) 5 min jogging followed by 3 min of rest (NS). After the protocols, the participants performed the following measurements: (a) force-matching test at 20% maximal isometric voluntary contraction (force sense), (b) active straight leg raise test (dynamic flexibility) and (c) reaction and movement time test. Results: Repeated measures analysis of variance revealed no significant main effects on force sense. Furthermore, SS performed significantly better in dynamic flexibility in comparison to NS, and DS performed significantly better in terms of dynamic flexibility and movement time compared to SS. Conclusion: According to the results of the study, it seems that force sense is not affected by either SS or DS protocols (30 sec duration per muscle group). Moreover, it seems that DS in the warm-up is more appropriate than SS for activities requiring dynamic flexibility and movement time.